Combating Human Trafficking In Vietnam: Lessons Learned and Practical Experiences for Future Program Design and Implementation - Quỹ Châu Á; Quỹ Châu Á
This report has been developed to share the achievements, experiences, best practices, and lessons learned from The Asia Foundation’s six-year program to prevent and combat human trafficking in Vietnam. The report features an overview culled from The Foundation’s experience in implementing program interventions in collaboration with an expanding network of local and international partners that share our commitment to bettering the lives of trafficking victims and protecting those at-risk of being trafficked.